Thermal Behaviors And Ionic Conductivity Of Composite Enr-50-Based Polymer Electrolytes - Tan, Wei Leng (2013)
The synthesis of polymer electrolytes (PEs) and composite polymer electrolytes (CPEs) using epoxidized natural rubber (ENR-50) as the host matrix and magnetite (Fe3O4) nanoparticles as the inorganic filler was carried out. These were characterized by FTIR, SEM/X-mapping, TEM, XRD, DSC, TGA and EIS. The influence of lithium salt, LiX (where X = BF4 -, I-, CF3SO3 -, COOCF3 - and ClO4 -) with various anions and iodide salt, MI (where M = Li+, Na+, K+ and Ag+) with different cations on the properties and degradation of PEs was investigated. This was followed by the study of the simultaneous presence of Fe3O4 nanoparticles in various LiX-ENR-50 PE systems. The study on sole Fe3O4/ENR-50 composites was also performed for comparison purposes. The trend in thermal stability and ionic conductivity of LiX-ENR-50 PEs is in the order of LiBF4 >> LiCF3SO3 ~ LiCOOCF3 > LiI >> LiClO4. The LiClO4 hardly dissociates and formed LiClO4 aggregates within the ENR-50 matrix that resulted in a PE with low thermal stability and low ionic conductivity. The LiCF3SO3, LiCOOCF3 and LiI exert moderate interactions with the ENR-50 and their respective PEs exhibit moderate ionic conductivity and thermal property. The occurrence of epoxide ring opening and complexation or cross-linking reactions in and between the ENR-50 chains that involve BF4 - ions have produced a LiBF4-ENR-50 PE with superior thermal stability and ionic conductivity as compared to other LiX-ENR-50 PEs studied in this work. The impedance properties of MI-ENR-50 PEs are closely related to the solubility, interaction and the outcome morphology of MI salt in the ENR-50. The solubility of MI salt in the ENR-50 follows the decreasing trend of LiI > NaI > KI > AgI. In PEs, the LiI mostly exists in ions and the Li+ are pseudo-crosslinked with the epoxide in the ENR-50 chains. Other MI salts are hardly dissociated in the ENR-50 which exert weak or no chemical interaction with the ENR-50. The thermal stability of ENR-50 in PEs is dependant on the type of metal in the MI salt. The alkali metal like Li, Na and K does not greatly influence the stability of ENR-50. Nonetheless, the presence of AgI destabilizes the ENR-50 in PE. The degradation of ENR-50 in LiClO4-, NaI- and KIENR- 50 PE is similar to purified ENR-50 due to weak salt-ENR-50 interaction. It initiates with first-order reaction (F1) followed by 3-dimensional diffusion control (D3) reaction. The presence of other salts in PE caused the degradation of ENR-50 to follow only a D3 type model.